2016
DOI: 10.1007/978-3-319-46565-4_12
|View full text |Cite
|
Sign up to set email alerts
|

Aspect-Based Sentiment Analysis Using a Two-Step Neural Network Architecture

Abstract: Sentiment analysis can be regarded as a relation extraction problem in which the sentiment of some opinion holder towards a certain aspect of a product, theme or event needs to be extracted. We present a novel neural architecture for sentiment analysis as a relation extraction problem that addresses this problem by dividing it into three subtasks: i) identification of aspect and opinion terms, ii) labeling of opinion terms with a sentiment, and iii) extraction of relations between opinion terms and aspect term… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…To build the distantly supervised models, we use untagged reviews which are about the 8 products of USAGE. The baseline systems are (Klinger and Cimiano, 2014) and (Jebbara and Cimiano, 2016), which are state-of-the-art systems on the dataset.…”
Section: Results On Usage Corpusmentioning
confidence: 99%
“…To build the distantly supervised models, we use untagged reviews which are about the 8 products of USAGE. The baseline systems are (Klinger and Cimiano, 2014) and (Jebbara and Cimiano, 2016), which are state-of-the-art systems on the dataset.…”
Section: Results On Usage Corpusmentioning
confidence: 99%
“…Previous work in the direction of aspect-based sentiment analysis shows a positive impact of POS tag features for the extraction of opinion phrases and opinion target expressions (Toh and Wang, 2014;Jebbara and Cimiano, 2016). It stands to reason if the character-level word embeddings act in a similar way.…”
Section: Discussionmentioning
confidence: 99%
“…The word embedding matrix W wrd is initialized with a pretrained matrix of skip-gram embeddings trained on a corpus of amazon reviews , 2015). Earlier work showed that using a domain specific corpus in the pretraining stage significantly improves performance for similar tasks (Jebbara and Cimiano, 2016).…”
Section: Network Trainingmentioning
confidence: 99%
“…Performing the same procedure with the regular skip-gram word embeddings results in no clear separation between the 6 suffix groups (see Figure 3b). Previous work in the direction of aspect-based sentiment analysis shows a positive impact of POS tag features for the extraction of opinion phrases and opinion target expressions (Toh and Wang, 2014;Jebbara and Cimiano, 2016). It stands to reason if the character-level word embeddings act in a similar way.…”
mentioning
confidence: 99%
“…The word embedding matrix W wrd is initialized with a pretrained matrix of skip-gram embeddings trained on a corpus of amazon reviews ( McAuley et al, 2015). Earlier work showed that using a domain specific corpus in the pretraining stage significantly improves performance for similar tasks (Jebbara and Cimiano, 2016). …”
mentioning
confidence: 99%